Surface contamination with ten antineoplastic drugs in 83 Canadian centers. (July 2019) - Chauchat, L; Tanguay, C; Caron, NJ; Gagné, S; Labrèche, F; Bussières, JF
Purpose: The aim of this study was to monitor environmental contamination by 10 antineoplastic drugs in Canadian oncology pharmacy and patient care areas. The secondary objective was to explore the impact of factors that may explain contamination. Methods: Twelve standardized sites were sampled in each center (six in the pharmacy and six in patient care areas). Each sample was prepared to allow quantification of seven antineoplastic drugs (cyclophosphamide, ifosfamide, methotrexate, cytarabine, gemcitabine, 5-fluorouracil, irinotecan) by UPLC-MS-MS. Docetaxel, paclitaxel and vinorelbine were also detected, but not quantified due to sensibility limitations. The impact of some factors was evaluated compared with a Kolmogorov–Smirnov test for independent samples. Results: Eighty-three Canadian centers were recruited in 2017. A total of 953 surfaces were sampled, 495 in pharmacy and 458 in patient care areas. Cyclophosphamide was most often found on surfaces (36% of samples positive, 75th percentile 0.0040 ng/cm 2 ). The arm rest (81.7% of samples positive for at least one antineoplastic drug), the front grille inside the hood (78.3%) and the floor in front of the hood (61.4%) were more frequently contaminated. Centers who prepared more antineoplastic drugs per year had higher concentration on different surfaces ( p < 0.0001). Conclusion: Despite growing awareness and implementation of new safe handling guidelines, healthcare centers' surfaces remain contaminated with traces of many antineoplastic drugs. The use of personal protective equipment remains indisputable. Performing an annual monitoring remains a good indicator to monitor trends over time and to compare with similar centers.